2012
DOI: 10.1021/ac301458e
|View full text |Cite
|
Sign up to set email alerts
|

Using Plasticizers to Control the Hydrocarbon Selectivity of a Poly(Methyl Methacrylate)-Coated Quartz Crystal Microbalance Sensor

Abstract: Chemical sensors based on a polymer coated quartz crystal microbalance (QCM) generally present poor molecular selectivity for compounds that contain similar functional groups and possess the same chemical properties. This paper shows for the first time that the selectivity and sensitivity of a poly(methyl methacrylate) (PMMA) based QCM sensor can be significantly enhanced for aromatic hydrocarbons by incorporating a plasticizer into the polymer film. The sensor was fabricated by spin coating PMMA onto a quartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Interestingly, the slope of the curve increases with hydrocarbon molecular weight and a possible reason for this may be due to the much higher analyte amount in the PIB film with increasing hydrocarbon hydrophobicity. This is consistent with recent reports which show that the hydrocarbon-polymer partition process increases in the following order: benzene < toluene < xylenes $ ethylbenzene < naphthalene (Pejcic et al, 2012). However, the observed relationship between the slope and hydrocarbon molecular weight is complicated by factors other than just concentration changes in the PIB film that arise from differences in the partition coefficient.…”
Section: Calibration and Sensitivity Determinationsupporting
confidence: 92%
“…Interestingly, the slope of the curve increases with hydrocarbon molecular weight and a possible reason for this may be due to the much higher analyte amount in the PIB film with increasing hydrocarbon hydrophobicity. This is consistent with recent reports which show that the hydrocarbon-polymer partition process increases in the following order: benzene < toluene < xylenes $ ethylbenzene < naphthalene (Pejcic et al, 2012). However, the observed relationship between the slope and hydrocarbon molecular weight is complicated by factors other than just concentration changes in the PIB film that arise from differences in the partition coefficient.…”
Section: Calibration and Sensitivity Determinationsupporting
confidence: 92%
“…This work investigates the equilibrium sorption of several solvents and the kinetic transport of water and short-chain alcohols in Matrimid 5218 using gravimetry and quartz crystal microbalance techniques. Quartz crystal microbalance is an excellent technique for measuring masses down to the order of nanograms and has been explored and applied for a variety of mass-sensitive uses including high pressure gas sorption [18,19,23], vapor sorption [13,24,25], chemical sensor applications [26,27], and ligand binding [28,29]. QCM was chosen for this work for its ability to examine films with thicknesses in the range of 0.05 to 5 µm, which crystal depends on crystal cut and thickness, each individual crystal has a unique fundamental frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Pejcic et al have shown good discrimination of benzene, toluene, ethylbenzene, xylene and naphthalene in water with four polymer coated quartz crystal microbalances 22 and improved limits of detection, between 400 and 4000 μg L −1 by altering the plasticizers. 7 They have also used MOF's to probe mixtures, but in neat solutions. 4 A biologically based sensor array that used fluorescent Escherichia coli discriminated between BTEX and other pollutants at concentrations of 44 000-220 000 μg L −1 .…”
Section: Analyst Papermentioning
confidence: 99%
“…Partially selective sensor arrays may become an attractive alternative to monitor groundwater. There are several partially selective sensing platforms that have been used to directly detect petroleum products in soil and water: fluorescent DNAbased chemosensors, 2 bacterial bioreporting assay sensors, 3 luminescence monitoring of interpenetrating metal organic frameworks (MOF), 4 preconcentration and chemicapacitive polymer detectors, 5 polymer coated thickness shear-mode resonators, 6,7 polymer coated surface acoustic wave (SAW) sensors, 8,9 siloxane clad optical fibre sensors, 10 polymer chemiresistors, 11 and graphene, carbon nanotube or gold nanoparticle chemiresistors. 12,13 These partially selective sensors must be deployed in arrays to discriminate and quantify the chemicals that they detect.…”
Section: Introductionmentioning
confidence: 99%